OPTIMALISASI KOMPETENSI PEMASARAN SISWA SMK NEGERI 1 CIRUAS MELALUI E-COMMERCE DAN MARKETPLACE - Susanto, Denies; Fuadi, Fuadi (Batara Wisnu : Indonesian Journal of Community Services, 2025)
This Community Service Program (PKM) aims to optimize the marketing competencies of students at SMK Negeri 1 Ciruas through an e-commerce and marketplace approach. The main challenge faced was the gap between the conventional curriculum and the digital competency demands of the Industrial Revolution 4.0 era. The implementation method included a series of theoretical and practical training sessions, transaction simulations, and ongoing mentoring focused on online store management, digital marketing strategies, and promotional content production. The program evaluation results showed significant improvements in students' understanding of e-commerce concepts and technical skills. Quantitatively, more than 80% of participants successfully demonstrated a deep understanding of basic e-commerce concepts, and all groups successfully created and activated online stores on marketplace platforms. In addition to improving technical competencies (hard skills), the program also contributed to the development of entrepreneurial soft skills such as communication, creativity, and time management. This program aligns with government policies to strengthen vocational education and digital literacy. It can be concluded that interventions through e-commerce and marketplaces are effective in increasing competitiveness and preparing vocational school graduates for the workforce, as well as developing a digital entrepreneurial spirit.